The relationship between change in perceived motivational climate and change in goal orientations among Japanese ice hockey players - Saotome, H.; Harada, K.; Nakamura, Y. (International Journal of Sports Science and Coaching, 2012)
The purpose of this study was to examine the relationship between change in the perceived motivational climate created by coaches and change in goal orientations over time among Japanese high-school ice hockey players. One hundred and forty-six players completed surveys twice over the course of the athletic season. The results showed that a change in task-involving climate was positively associated with change in task orientation over the course of the season. Changes in both task-involving climate and ego-involving climate were positively associated with change in ego orientation over time. These results demonstrated that the task-involving climate created by coaches may influence not only players' task goal orientations but also their ego orientation in Japanese youth sports settings. On the other hand, an ego-involving climate created by coaches may influence players' ego goal orientations.